2017
DOI: 10.1155/2017/7396462
|View full text |Cite
|
Sign up to set email alerts
|

Normal versus Pathological Cardiac Fibroblast-Derived Extracellular Matrix Differentially Modulates Cardiosphere-Derived Cell Paracrine Properties and Commitment

Abstract: Human resident cardiac progenitor cells (CPCs) isolated as cardiosphere-derived cells (CDCs) are under clinical evaluation as a therapeutic product for cardiac regenerative medicine. Unfortunately, limited engraftment and differentiation potential of transplanted cells significantly hamper therapeutic success. Moreover, maladaptive remodelling of the extracellular matrix (ECM) during heart failure progression provides impaired biological and mechanical signals to cardiac cells, including CPCs. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
(65 reference statements)
0
20
0
1
Order By: Relevance
“…In addition to tissue derived dECM, there have been studies on cardiac‐specific dECM derived from cardiac fibroblasts grown in sheets, called fibroblast‐derived matrix (FDM) . These scaffolds can be used as patches, either directly or with additional cell seeing.…”
Section: Solid Decmmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to tissue derived dECM, there have been studies on cardiac‐specific dECM derived from cardiac fibroblasts grown in sheets, called fibroblast‐derived matrix (FDM) . These scaffolds can be used as patches, either directly or with additional cell seeing.…”
Section: Solid Decmmentioning
confidence: 99%
“…In addition, by altering crosslinking of the FDM to increase stiffness, there were further increases in cardiogenic differentiation, with α5 integrin expression increased on crosslinked compared to non‐crosslinked FDM. In a cardiac‐specific method, Pagano et al grew CPCs isolated as cardiosphere‐derived cells (CDCs) on FDM derived from fibroblasts harvested from healthy and infarcted hearts . After 7 d in culture, both systems showed expression of cardiac differentiation, although CDCs on healthy FDM secreted higher levels of reparative factors such as osteopontin, FGF, IGF, and TIMP‐2, modeling the decrease in reparative and antiremodeling potential of CDCs when injected in an infarct environment.…”
Section: Solid Decmmentioning
confidence: 99%
“…Despite the synergistic effect of all ECM components, a direct supporting mechanism has been already reported for some ECM molecules like fibronectin, proven to be necessary for endogenous CPC proliferation and activation for repair through focal adhesion signaling . The ECM's influence on CPCs, though, may act at multiple levels: we have previously reported that human CPCs cultured short‐term on cardiac fibroblast‐derived ECM substrates from failing hearts release less trophic and anti‐remodeling paracrine factors, such as tissue inhibitor of metalloproteinases 2 (TIMP2), compared to substrates from fibroblasts from healthy hearts . Moreover, multiple studies have investigated several combinations of ECM protein substrates (e.g., fibronectin, laminin, collagen) with variable mechanical stimuli (e.g., cyclic strain), suggesting that mechanical and biological signals can compensate and modulate each other in different proportions , making it very difficult to design an artificial matrix from scratch.…”
Section: Regenerating the Myocardium By The “Right” Matrixmentioning
confidence: 99%
“…Кроме того, именно состояние белков матрикса определяет регенеративные свойства ПКС. Культивирование ПКС на матриксе, наработанном клетками пациентов с хронической сердечной недостаточностью, вызывает подавление их паракринной активности по сравнению с матриксом от здоровых доноров [27]. Более того, в нескольких исследованиях продемонстрировано, что соотношение компонентов внеклеточного матрикса и их модификация являются определяющим фактором для запуска регенеративной программы в прогениторных клетках [28,29].…”
Section: а б вunclassified